Effectiveness of Socialization of Making Rat Traps in Efforts to Control Rat Vectors Among Housewives in Bandar Setia Village - Yulia Khairina Ashar; Ni’matul Ulya Munthe; Nurul Indah Nasution; Rafiqoh Hasibuan; Rahmaidah Pohan; Siti Nur Aisyah; Tri Wulandari (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2025)
Leptospirosis is a zoonotic disease that has the potential to cause an epidemic and is widespread globally. The mortality rate from this disease is quite high, ranging from 9.1% to 11.4% in Indonesia. This study aims to determine the effectiveness of socialization of making Rat Traps on the knowledge of targets (Housewives) about efforts to control the population of Leptospirosis disease Rat vectors. The experimental method in the form of a single case pretest-posttest design was used as a method in this study. To measure the success of the activity, a Pre-Test and Post-Test will be distributed with a questionnaire instrument before and after the socialization. The results obtained were an increase in target knowledge by 84% after socialization, with an average value before socialization of 5 and after socialization increasing to 9.2. So that the Ngain score value was 0.84 and the Ngain Score (%) 84.1% was obtained, which means that the Socialization of Making Ovitrap has an effectiveness in increasing the knowledge of Housewives in Hamlet 5, Bandar Setia Village. The conclusion in this study is that the socialization carried out has an effective benefit in increasing the knowledge and awareness of target activities in efforts to control Rat Vectors. Researchers suggest that the Head of the Environment and those responsible for the community continue to monitor developments in understanding regarding Rat Vector Control.